Insights into design of mobility control for chemical enhanced oil recovery - R. Farajzadeh; B. L. Wassing; L. W. Lake (Energy Reports, 2019)
Synthetic fuels produced with renewable surplus electricity depict an interesting solution for the decarbonization of mobility and transportation applications which are not suited for electrification. With the objective to compare various synthetic fuels, an analysis of all the energy conversion steps is conducted from the electricity source, i.e., wind-, solar-, or hydro-power, to the final application, i.e., a vehicle driving a certain number of miles. The investigated fuels are hydrogen, methane, methanol, dimethyl ether and Diesel. While their production process is analyzed based on literature, the usage of these fuels is analyzed based on chassis dynanometer measurement data of various EURO-6b passenger vehicles. Conventional and hybrid power-trains as well as various carbon dioxide sources are investigated in two scenarios. The first reference scenario considers market-ready technology only, while the second future scenario considers technology which is currently being developed in industry and assumed to be market-ready in near future. With the results derived in this study and with consideration of boundary conditions, i.e., availability of infrastructure, storage technology of gaseous fuels, energy density requirements, etc., the most energy efficient of the corresponding suitable synthetic fuels can be chosenThis study compares two methods of mobility-control design for chemical enhanced oil recovery processes. Method 1 matches the total relative fluid mobility upstream and downstream of the shock front. In method 2 the viscosity of the displacing agent is selected such that the total mobility at the shock water saturation is equal to or less than the minimum mobility across the saturation range. The two methods are based on fractional flow analysis of one-dimensional flow and they are validated against two-dimensional simulations of flow through heterogeneous permeable media. Our results emphasize the key role of the water/oil relative permeability curves for the design of mobility control in polymer and surfactant/polymer flooding. The polymer viscosity obtained by setting the shock-front mobility ratio to one (method 1) is the minimum viscosity to ensure a stable displacement front. Design by method 2 results in a larger viscosity than method 1. This shifts the shock water saturation to larger values and hence more oil is displaced. Moreover, we find that for surfactant-polymer (SP) solutions with ultra-low interfacial tension (IFT) reduction (Winsor type III), the required polymer viscosity is always greater than the oil viscosity (at low shear rates). However, for Winsor type I solutions, for oils with medium and large viscosity the non-linear shape of the relative permeability function leads to polymer viscosities that are less than that of the oil. For light oils the viscosity of the ASP solution should be significantly larger than the oil viscosity.
Keywords: 330